10x - 3 = x + 2 + 2x - 1
10x - 3 = 3x + 1
-3x on both sides
7x - 3 = 1
-1 on both sides
7x - 4
(Check 7x - 4 by adding them all up to equal 10x - 3)
x + 2 + 2x - 1 + 7x - 4 = 10x - 3
combine liked terms
10x - 3 = 10x - 3
Answer:
D) 7x - 4
D because counterclockwise is turning to your left
Answer:
Ellen invested $60 and Bob invested $140
Step-by-step explanation:
let the two amounts invested by 3x and 7x
(notice 3x : 7x = 3 : 7 )
then 3x + 7x = 200
10x = 200
x = 20
then 3x = 3(20) = 60
and 7x = 7(20) = 140
60+140=200
Answer:
D = 4, Z = 24
Step-by-step explanation:
6D+3Z = 96
5D+4Z = 116
multiply top by 5 and bottom by -6
top equation = 30D+15Z = 480
bottom equation = -30D-24Z = -696
Cancel 30D and -30 D
top equation = 15Z = 480
Bottom equation = -24Z = -696
15Z - 24 Z = 480 - 696
-9Z = 216
Z = 216/9
Z = 24
Now that we have the value of Z, we can substitute it in any equation to find D
6D + 3(24) = 96
6D + 72 = 96
6D = 96 - 72
6D = 24
D = 24/6
D = 4